Geomics as Interactive Geography Learning Media: A Development Study on Environmental Material in High Schools - Muis, Abdul; Pholboon, Monton; Kamali, Ahmad Nur (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to develop geography comic media on environmental material for class XI students of Sultan Agung 1 Islamic Senior High School, Semarang. Methodology: The methodology used in this study is Research and Development (R&D) with a One-Group Pretest-Posttest Design. The tools used include multiple-choice tests, student response questionnaires, and media validation questionnaires. Data analysis software uses descriptive statistics and validity-reliability tests. Media feasibility assessments are carried out through reviews by material and media experts, as well as student response surveys. Main Findings: The results of media expert validation showed that geography comic media (GEOMIK) was very feasible to use with a feasibility percentage of 89.06%. Material expert validation showed a feasibility of 78.12%, and geography teachers 92.18%. Student responses stated that the media was very interesting with a percentage of 83.24%. Student learning outcomes increased from an average of 65.29 to 81.81 after using the media. Novelty/Originality of this study: The results of this study support the use of GEOMIK as an effective learning media in improving student learning outcomes in environmental material. This media is not only visually appealing but is also able to convey information in a way that is easy to understand, increase student engagement in learning, and help students develop a deeper understanding of the topics being studied.